Business mathematics a complete textbook and workbook - Mejia, Leila DP; Gabuyo, Yonardo A.; Ignacio, Jayme C.; Sajise, Jess Jay M. (Books Atbp. Pub., 2008)
"Designed for the students who wish to master the quantitative principles and techniques in business needed for sound decision-making. This book serves as preparation for higher business mathematics and related coruses or as an end in itself. Upon completion of this course, students will realize that studying business mathematics could be an enjoyable experience, as well as wisdom that should be treasured for life."--Preface.